Effect of carbon/nitrogen ratio manipulation in feed supplements on Artemia production and water quality in solar salt ponds in the Mekong Delta, Vietnam. Issue 12 (14th February 2013) - Ronald, Lulijwa; Van Stappen, Gilbert; Van Hoa, Nguyen; Sorgeloos, Patrick
Abstract The effect of carbon/nitrogen (C/N) ratio manipulation in feed supplements on Artemia production and water quality was investigated in solar salt ponds in the Mekong Delta, Vietnam. It was assumed that development of bacterial bioflocs through C/N manipulation would improve Artemia production and water quality as demonstrated in freshwater and marine aquaculture. Twelve ponds were used for three treatments and the control, in triplicates. Green water (GW) was supplied to all ponds, with the standard Vietnamese procedure of supplying GW and chicken manure (CM) as the control (C/N 1.8). Treatment ponds were supplemented with tapioca (TAP) as carbon source, combined with either CM, pig manure (PM) or rice bran (RB), with C/N ratios of 7.4, 10.5 or 20.1 respectively. After 6 weeks of culture, no single treatment supported both improved water quality and enhanced Artemia production. Overall, improved water quality was observed at C/N 20.1 and higher Artemia production at C/N 7.4. Although external field factors could have interfered with the set‐up, this is the first study on the effect of C/N manipulation in feed supplements in Artemia pond production systems and provides the basis for development of bacterial bioflocs as a technology to improve water quality and Artemia production.